(3GdJbQjH hGdJjSjQ deYQaI Sff GdHTjQ hGdfPjQs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3YKeGf Hf YHO GdQMef (B((3UdGM GdOjf(B) (3GHf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, CHh YeQh, Jbj GdOjf, GdeYQha HGHf GdUdGM,J (B643 (3g` s ((3OGhO Hf GZdHc Hf Ydi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdaJGM GdefGf CeG HYO aEf Yde GdMOjK ef CaVd GdbQH Edi QH GdYGdejf hgPG cJGH GNJUQJg ef cJGH GdGQTGO GdPi GNJUQJg ef Ydhe GdMOjK ddTjN CHh YeQh YKeGf Hf YHO GdQMef GdeYQha HGHf GdUdGM GdMOjK UMjM hMSf hVYja s
(3BNQgG (B:s
(3hbO QhjJ ai GdGQTGO gfG KdGKI GMGOjK HCSGfjO cdge OeTbjhf efi Edi QShd Gdgd Udi Gddg Ydjg hSde hGf OeTbi MeGgG JYGdi hUGfgG hSGFQ HdGO GdGSdGe hCgdg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B257s
Keywords: (3GdMOjK h GdeUWdMs